A study of telecommunication tower verticality eccentricity by using reflectorless total station and unmanned aerial vehicle - Teoh, Joshua (2022)
An aerial survey utilising a drone or other unmanned aerial vehicle (UAV) can give a quick and effective way to collect data across tall structures in a short amount of time. Inspection surveys using UAV enable safer access to assets that are hazardous, dangerous, or difficult to access, such as high-voltage powerlines and towers, flare stacks on and offshore, and high-rise structures. UAV inspections lessen the risk to employees by placing the operator in a safer setting than would be the case if the same operation were done manually. The number of visits and workers necessary to the site is reduced by providing a selection of products that can be shared and seen several times in the office by engineers, making the works safer. UAVs were created as a result of low-altitude photogrammetric mapping to improve aerial photography accuracy and image resolution. As a result, the goal of this research is to use a UAV and a reflectorless total station to manage the verticality eccentricity of a telecommunication tower. Before taking an aerial photograph using a UAV, several factors were carefully addressed, including image resolution, flying height, flying radius, and speed to fly on the site area to eliminate natural errors. Before merging and defining the different of the error based on the eccentricity, a systematic produce was carried out, for example, reflectorless total station and UAV survey. The reflectorless total station will be used to acquire the vertical eccentricity of the tower drawing, which will then be examined using AutoCAD software. The UAV will provide digital photographs, which will be processed using Pix4D software. The final stage will be to define the 3D model once all of the data has been analysed. The surveyor can define the structure of the tower in Pix4D software by exporting the polyline to AutoCAD software. As a result, surveyors can calculate the verticality eccentricity based on the tower's ground platform and analytical mistakes for each tier.